Biosafety Level at the Microbiology Laboratory of PT SCI - Rakhman, Aulia Jauhari; Nasri, Sjahrul Meizar (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Introduction: Protection of personnel in microbiological testing laboratories should be conducted. One of the efforts that can be used for preventive action is the determination of the biosafety level. This study was conducted with the aim of knowing how important the biosafety level is seen from the readiness level of laboratory personnel regarding knowledge, training, and competency assessment of laboratory personnel. Moreover, this study was also based on the application of biological risk assessment and the planned biosafety implementation program. Method: The sampling method used was secondary data with document review and data recording from the implementation of activities in the microbiology laboratory. Meanwhile, the primary data collection was done through in-depth interviews with respondents using questionnaires and direct interviews. Result: The results of data collection and data processing showed that 74% of laboratory personnel had the appropriate competence in carrying out the assessment by determining the biosafety level. This was supported by the biosafety program which might be planned and implemented with laboratory readiness. This had a percentage of 73% in terms of biological risk assessment and laboratory facilities. Conclusion: Determination of biosafety level is important for personnel who is working in dangerous facilities which is exposed to microbiological agents such as bacteria, viruses, fungi, and other microbiological products. This is because, determining the biosafety level not only protects laboratory personnel, but also the environment from biological hazards.